Algorithm for evaluation of turbulence polarimetric weather radar - Авер’янова, Ю.А.; Аверьянов, A.А.; Яновський, Ф.Й. (Proceedings of National Aviation University (archive), 2009)
A new approach for turbulence intensity estimate with polarimetric weather radar is considered and analyzed. The algorithm of turbulence estimate with polarization spectrum components of reflected from weather object signal is developed and shown.